Caveolin-1 Is Essential for the Improvement of Insulin Sensitivity through AKT Activation during Glargine Treatment on Diabetic Mice. (7th December 2021) - Peng, Hangya; Mu, Panwei; Li, Haicheng; Lin, Shuo; Lin, Chuwen; Lin, Keyi; Liu, Kunying; Zeng, Wen; Zeng, Longyi
Abstract : Insulin treatment was confirmed to reduce insulin resistance, but the underlying mechanism remains unknown. Caveolin-1 (Cav-1) is a functional protein of the membrane lipid rafts, known as caveolae, and is widely expressed in mammalian adipose tissue. There is increasing evidence that show the involvement of Cav-1 in the AKT activation, which is responsible for insulin sensitivity. Our aim was to investigate the effect of Cav-1 depletion on insulin sensitivity and AKT activation in glargine-treated type 2 diabetic mice. Mice were exposed to a high-fat diet and subject to intraperitoneal injection of streptozotocin to induce diabetes. Next, glargine was administered to treat T2DM mice for 3 weeks (insulin group). The expression of Cav-1 was then silenced by injecting lentiviral-vectored short hairpin RNA (shRNA) through the tail vein of glargine-treated T2DM mice (CAV1-shRNA group), while scramble virus injection was used as a negative control (Ctrl-shRNA group). The results showed that glargine was able to upregulate the expression of PI3K and activate serine phosphorylation of AKT through the upregulation of Cav-1 expression in paraepididymal adipose tissue of the insulin group. However, glargine treatment could not activate AKT pathway in Cav-1 silenced diabetic mice. These results suggest that Cav-1 is essential for the activation of AKT and improving insulin sensitivity in type 2 diabetic mice during glargine treatment.